2017
DOI: 10.1371/journal.pone.0177756
|View full text |Cite
|
Sign up to set email alerts
|

Quality of maternity care and its determinants along the continuum in Kenya: A structural equation modeling analysis

Abstract: BackgroundImproving access to delivery services does not guarantee access to quality obstetric care and better survival, and therefore, concerns for quality of maternal and newborn care in low- and middle-income countries have been raised. Our study explored characteristics associated with the quality of initial assessment, intrapartum, and immediate postpartum and newborn care, and further assessed the relationships along the continuum of care.MethodsThe 2010 Service Provision Assessment data of Kenya for 627… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 30 publications
8
44
0
Order By: Relevance
“…The 2000 World Health Report devoted substantial portions to making health systems respond to users’ expectations [ 11 ]. Following the report, studies on health systems responsiveness, in part, viewed as the quality of care has increased in the last two decades [ 12 , 13 ]. Quality of health care is generally framed as the level of service provision that meets the expectations of individuals and patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2000 World Health Report devoted substantial portions to making health systems respond to users’ expectations [ 11 ]. Following the report, studies on health systems responsiveness, in part, viewed as the quality of care has increased in the last two decades [ 12 , 13 ]. Quality of health care is generally framed as the level of service provision that meets the expectations of individuals and patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used both descriptive and logistic regression for complex survey were carried out to assess determinants of ARI symptoms. We ensured national representativeness; weighting factors were employed in this study to adjust for over sampling of some areas and under-sampling of others in the Demographic and Health Survey by using sampling weights using Taylor series linearization method [ 48 , 49 ]. Structurally, two indicators of inequality in the distribution of ARI symptoms namely Gini index [ 50 ] and Concentration index [ 51 ] were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, adverse outcomes were thought to result primarily from delivery occurring outside of health facilities and from lack of access to skilled care [3][4]. However, a recent literature review showed more women in low income countries are delivering in facilities but this shift has not been consistently linked to mortality reduction nor guaranteed that appropriate interventions are rendered during the intra-partum and immediate postpartum period in settings which may result in low quality of care (QoC) [5][6][7]. Strategies such as the Janani Suraksha Yojana (JSY) program, a large conditional cash transfer programs in India, have increased rates of facility-based childbirth without significantly decreasing maternal and neonatal mortality [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent literature review showed more women in low income countries are delivering in facilities but this shift has not been consistently linked to mortality reduction nor guaranteed that appropriate interventions are rendered during the intra-partum and immediate postpartum period in settings which may result in low quality of care (QoC) [5][6][7]. Strategies such as the Janani Suraksha Yojana (JSY) program, a large conditional cash transfer programs in India, have increased rates of facility-based childbirth without significantly decreasing maternal and neonatal mortality [6,8]. This finding implies improving the QoC provided during facilitybased childbirth is key to decreasing maternal and neonatal mortality and complications [9,10].…”
Section: Introductionmentioning
confidence: 99%